IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPS TERPADU DI SMP UTAMA BAKTI PALEMBANG - Eva Dwi Sartika; Cik Ima (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
This research was conducted with the aim to see the implementation of the existing materials in integrated IPS learning at SMP Utama Bakti Palembang. The method used is qualitative research with phenomenology design. The results obtained from the research that has been done is integrated IPS subject teachers have done a good stage in the framework of optimizing character education in the learning process. This is evidenced by the planning stages of learning devices that have analyzed each value or character in the learning process, ranging from SK, KD, to RPP and learning materials. So even in the implementation of learning that has been achieved, religion, honesty, responsibility, discipline, and communicative. Implementation of character education is also supported by the school culture that to improve the exemplary starting from the tidiness of dress, the time discipline tells about the customs of the ceremony and before learning.